Improvement of Usability Issues in WAP - Alhamwi, Srii Mamdouh (2009)
This master's thesis considers study on the usability issues in the WAP application and it focused on the navigating aspect. The thesis is a theory-testing research consisting of two parts. The first part forms the frame of reference for the empirical theory-testing experiment. By reading the conceptual theoretical background research one can form a general picture of the current usability in the WAP applications and the recent research considering navigation structures in mobile environment. The second part of this thesis describes the controlled experiment, which is a comparative usability testing of two different WAP applications. The purpose was to improve the usability issues in the WAP application and discover, whether the placing of the links or select down button has an impact on the usability of WAP applications. Also, the effects of the possibility to cross-navigate were tested. When analyzing the results, it was noticed that select down button technique created more speed to navigate and reduced a lot of complexity in the WAP applications. The first WAP application, where navigation is list of links, suffered from severe usability problems. The second WAP application, where navigation happened through select down button and paging technique, is preferable in all evaluated aspects: learnability, errors, efficiency of use, subjective satisfaction and the user's awareness of her/his current position in the application. The results are exploitable in the WAP application development in general, and especially when considering the further development of Islamic digital library, benefits from the results, when generating their guidelines for mobile application developers.